Avaliação ambiental-econômica do uso da energia no processo de produção de água mineral com aplicação dos conceitos de produção mais limpa - Anschau, Ramon (Universidade do Vale do Rio dos Sinos, 2018)
The increase in mineral water consumption shows the concern of the world population with the purchase of healthier products. However, due to the small financial margin with the sale of the product, there is greater competitiveness among companies and the use of resources for the production processes must be known and minimized, without impacting on quality. The objective of this research was to understand and stratify energy consumption in the different stages of the production process of non-carbonated mineral water in 500 ml packages, seeking to apply improvements through Cleaner Production (P+L) concepts. Knowing the potential environmental impacts of the main stages of the production process was also one of the objectives of the study. For this, the main and auxiliary processes were detailed through input and output flow charts, and the Environmental Aspects and Impacts Survey (LAIA) was subsequently carried out. Performance indicators were defined, monitored and compared with the bibliography at the end of the study, which guided discussions between the different areas of the company. All actions were evaluated technically and economically through periodic meetings and with simple Payback calculations, making it possible to know the feasibility of possible investments. At the end of the study were presented the improvement opportunities implemented which brought significant gains. After evidencing that approximately 70% of the energy consumption is necessary for the manufacture of the packaging, one of the suggested improvements was the manufacture of lighter preforms. This made the process 8% more energetically efficient, besides contributing to the possibility of reducing up to 195 tons of PET resin per year, which brought economic gains, as well as reducing the generation of solid waste. The reduction in blowing pressure, another improvement implemented, generated a 23% reduction in energy consumption associated with the generation of high pressure compressed air. Process improvement with payback of 6 months generated annual savings of about R$37.000,00 considering the average of the tariff paid by the southern region of Brazil, where the company is located. With the use of these methods, this research aimed to demonstrate the potential for increased efficiency that these tools can bring to companies, bringing, in addition to environmental and economic benefits, to strengthen the continuation of other case studies with the same approach, since it works at all hierarchical levels of the organization.
Keywords: Água mineral; Garrafa PET; Energia; Produção mais limpa; Mineral water; PET bottle; Energy; Cleaner production; ACCNPQ::Engenharias::Engenharia Mecânica